Leveraging triple helix and system intermediaries to enhance effectiveness of protected spaces and strategic niche management for transitioning to circular economy. (1st March 2017) - Barrie, Jack; Zawdie, Girma; João, Elsa
The transition to circular economy has been heralded as a vision to overcome the challenges of rapid population growth, economic stagnation and environmental degradation. A promising policy tool for accelerating such a transition is strategic niche management (SNM), the central tenet of which is the formation of 'protected spaces' to support the growth of sustainable innovation. Studies have demonstrated that current top–down policy approaches to governing protected spaces have led to the unintended consequences of network tensions, low quality learning processes and low innovation adoption rates outside protected spaces. This limits the impact of SNM as a transition tool. Through a detailed literature review, this article looks into a novel devolved governance framework for protected spaces in the context of transition to circular economy. The framework addresses current limitations of SNM by acknowledging the synergistic relationship with the triple helix innovation system; and innovation intermediation. Transition to circular economy turns on the achievement of 'triple helix consensus' across 'protected spaces' to provide the requisite platform for sustained innovation and for the recurrent choice of knowledge and market systems that are consistent with the circular economy growth trajectory.